Restorative experience perceived by the users - Hussain, Norhuzailin; Abdul Aziz, Faziawati (e-International Publishing House (e-IPH), 2018)
The recreational forests are facing pressure by surrounding developments such as highway and housing. Urban development has implications for the benefits offered by recreational forests, endangered biodiversity, water quality and wildlife to result a place that is no longer enjoyable to visit. It is important to conserve the recreational forests that can contribute to the urbanites quality of life. Based on the results from the site observations, self-administered questionnaires and in-depth interviews at two recreational forests (The Ampang and Kanching Recreational Forests), this paper describes recreational forest users’ experience and what makes they perceived restored while being in the forest.